Mental toughness between elite Egyptian athletics players - comparative study - Naglaa, E.; Larion, A.; Abeer, M.; Amr, H. (Science, Movement & Health, 2017)
Aim. Trainers and athletes emphasize that psychological skills that reflect mental toughnesscontribute at least 50% to achieving athletic achievement. Mental toughness is the most important in achieving athletic achievement. The purpose of this study was to validity and reliability the Egyptian version of Sport Mental Toughness Questionnaire" (SMTQ-14) and evaluate the mental toughness between elite athletics (track and field). Methods. 126 athletes (female and male) from (soccer, basketball, volleyball, athletics, swimming) to validity and reliability of Sport Mental Toughness Questionnaire" (SMTQ-14) The main sample contains Fifty-four athletics players from national team in Egypt participated in this study. (thirty-three players from track events (twenty-one male+ twelve female). twenty-one players from field events (fourteen male+ seven female). Results. Statistical analyses showed that: significantly different (p = < .05)in subscales; confidence, constancy andTotal SMTQ- 14 for track event players. No significantly different (p = > .05)in control variable. Conclusions. Under the conditions of our study, mental toughness differ according the event type. These results have to be taken into account by instructors in order to better understand and implicated of these concepts for technical effects of training.